2015
DOI: 10.1200/jop.2014.001842
|View full text |Cite
|
Sign up to set email alerts
|

Administration of Oral Chemotherapy: Results From Three Rounds of the Quality Oncology Practice Initiative

Abstract: The collection of oral chemotherapy test measure data is feasible. Composite scores for treatment plan documentation and patient education were not only lower, but had greater variability compared with adherence/toxicity monitoring. Improvement opportunities exist for patients who are prescribed oral chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 36 publications
(28 reference statements)
0
13
0
2
Order By: Relevance
“…A review of practice-level systems indicated opportunities for quality improvement efforts for the safe management of chemotherapy, defining the treatment gap targeted here. 22…”
Section: Chemotherapy Education and Informed Consentmentioning
confidence: 99%
“…A review of practice-level systems indicated opportunities for quality improvement efforts for the safe management of chemotherapy, defining the treatment gap targeted here. 22…”
Section: Chemotherapy Education and Informed Consentmentioning
confidence: 99%
“…A review of practice-level systems indicated opportunities for quality improvement efforts for the safe management of chemotherapy, defining the treatment gap targeted here. 22 Perioperative MRI For high-grade gliomas, extent of resection is strongly correlated with overall survival. 23,24 Furthermore, many clinical trials include measures of residual disease as a criterion for inclusion.…”
Section: Chemotherapy Education and Informed Consentmentioning
confidence: 99%
“…Consequently there are concerns regarding adherence and management of toxicities or adverse effects (Greer et al, 2016;Hammond et al, 2012;NCCP, 2018;Paolella et al, 2018;Wood, 2012). Evidence suggests that current health care practices globally do not ensure safe administration or patient adherence (Griffiths & Pasco, 2014;LeFebvre & Felice, 2016;Le Saux et al, 2018;Redelico et al, 2018;Zerillo et al, 2015). Following a review of OAM practices in North America, Zerillo et al (2015) identified unmet patient needs of 43-49% for patient education and 19-25% for adherence/toxicity monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that current health care practices globally do not ensure safe administration or patient adherence (Griffiths & Pasco, 2014;LeFebvre & Felice, 2016;Le Saux et al, 2018;Redelico et al, 2018;Zerillo et al, 2015). Following a review of OAM practices in North America, Zerillo et al (2015) identified unmet patient needs of 43-49% for patient education and 19-25% for adherence/toxicity monitoring. Individuals prescribed OAMs often experience a high burden of cancer related symptoms which corresponds to reduced adherence and quality of life (Jacobs et al, 2019).…”
Section: Introductionmentioning
confidence: 99%